Chemical species from diethylene glycol-dimethyl ether/argon discharges investigated at low pressure by mass spectrometry - Moreira, P. W.P. [UNESP]; Mota, R. P. [UNESP]; Honda, R. Y. [UNESP] (Elsevier, 2015)
Mass spectrometry is an important technique to investigate vacuum and discharges maintained at low or high pressure. It has been used to investigate plasma discharges from organic and inorganic gases or vapors. Plasma of organic gases or vapor can produce materials with interesting technological application. In this work, it was used to investigate the plasma discharges from diethylene glycol dimethyl-ether (diglyme)/argon at low pressure. The discharges occurred in a cylindrical stainless steel reactor, excited at 13.56 MHz from 10 Pa to 30 Pa as a function of partial pressure of the diglyme/argon mixture for different radio frequency powers between 1 and 40 W. The species assigned to H+ (m/z = 1), CH3+ (m/z = 15), CHO+ (m/z = 29), CH3O+ (m/z = 31), CH2CH2O+ (m/z = 44) and CH3OCH2CH2+ (m/z = 59) were investigated. The molecular structure of the films produced from these plasmas was analyzed by FTIR spectroscopy technique presenting C-O; C-O-C; C-H; C=C and O-H bonds.
Keywords: Argon; Diethylene glycol dimethyl-ether; Discharge; Mass spectrometry; Molecular structure; Plasma polymer